Analisis Pengetahuan Siswa SMA Terhadap Keselamatan Kerja di Laboratorium - Mila Trisna; R. Susanti Susanti; Retno Sri Iswari (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: A laboratory is a learning tool for conducting experiments or observations. Knowledge of workplace safety procedures and laboratory tools and materials can simplify and streamline the learning process. This study aims to analyze the knowledge of high school students on laboratory work safety material. Methods: This study is a quantitative study, namely research that describes students' knowledge of laboratory work safety. The research subjects were students of class X MIA 1 and MIA 2 SMAN 7 Jambi City, class X students of SMAS Insan Madani Jambi. Primary data on students' abilities about work safety in the laboratory were measured by a multiple-choice test consisting of 4 alternative choices, namely A, B, C, and D. Secondary data were taken by using an interview sheet for class X biology. Data were analyzed according to Miles and Huberman, namely data reduction, display data, and conclusions. Results: High school students' knowledge of work safety materials in the laboratory is still low, namely 61.86%. Students' knowledge of how to use the tools and their functions showed the lowest percentage, namely 55.36% (poor category), while the safety aspect of laboratory work showed the highest percentage, namely 73.71% (sufficient category). Conclusion: High school students have low knowledge in understanding work safety material in the laboratory. It is necessary to deepen the material so that students' knowledge of laboratory work safety increases.